The use of birthweight and gestation to assess perinatal mortality risk. Issue 3 (September 1979) - Hellier, J L; Goldstein, H
Abstract : Using extensive international data it is shown in detail how mortality is related to birthweight and gestation. It is demonstrated that the widely used 'birthweight for length of gestation' standards can be seriously misleading. A new 'high risk' classification is proposed.